Penatalaksanaan Fisioterapi Pada Fraktur Humeri 1/3 Proksimal Sinistra Di RSUD Sragen - PAMBUDI, Bagus (2015)
Background : Proximal one-third humeral sinistra fractures is a continuity broken of the bone structure that is located on the upper 1/3 of the left side portion of the humeral bone. Open Reduction Internal Fixation (ORIF) with Plate and Screw is an internal fixation surgery with the installation of the bone fracture, with plate and screw in the plug which serves to maintain bone fregmen position so as not to shift and will remain united. In the fracture condition with mounting plate and screw cause problems such as pain , limitation of motion , and decreased muscle strength. Objective : To investigate the implementation of physiotherapy in reducing pain , increasing range of motion limitations , and improve muscle strength in 1/3 proximal humeral fractures with the use of Infra Red (IR) and Exercise Therapy (TL). Results : After six times of treatment, results of the assessment of pain in tenderness T1 : 72 to T6 : 54 , motion pain : T1 : 78 into T6 : 58. Increased range of motion S : T1 : 50-0 - 85 to T6 : 50-0 - 100, F : T1 : 85-0 - 60 to T6 : 90 - 0-65 , T : T1 : 5 - 0-90 into T6 : 5 - 0-105 , R ( F = 0 ) : T1 : 40 - 0- 90 into T6 : 45 - 0-90 , R ( F = 90 ) : T1 : 80 - 0 - 45 to 85 - 0 - 45. The strength of flexor muscles of shoulder T1 : 4- become T6 : 4- , shoulder extensor T1 : 4 to T6 : 4 , shoulder adductor T1 : 4 to T6 : 4 , shoulder abductor T1 : 4- become T6 : 4 , eksorotator shoulder T1 : 4 to T6 : 4 , endorotator shoulder T1 : 4 to T6 : 4 . Conclusion : Infra Red (IR) and Therapeutic Exercise (TL) can reduce the pain , improve LGS , and improve muscle in the left shoulder strength in the one -third proximal of the humeral fracture conditions .